An annotated list of lichen-forming and lichenicolous fungi of Lugans’ky natural reserve (CHORNOMORSKI BOTANICAL JOURNAL, 2010)
List of lichens and lichenicolous fungi of Lugans’ky Natural Reserve consists of 160 species, which belong to 71 genera, 30 families and 8 orders of Ascomycota, including 29 species new for Reserve. In Stanychno-Lugans’ke branch 70 species, in Stril’tsivs’ka steppe – 28 species, in Proval’s’ka steppe – 126 species and in Trekhizbens’ka steppe – 51 species are revealed. Ecological and substrate features as well as the distribution in branches of the Reserve are given for each taxon.
Keywords: sandstone, bark of trees, soil, Caloplaca, Cladonia, Lecanora, Proval’s’ka steppe, Trehizbens’ka steppe, Strіl’tsіvs’ka steppe, Stanychno-Lugans’k department.